Overview and update on cytomegalovirus-associated anterior uveitis and glaucoma - Ye, Zifan; Yang, Yumei; Ke, Weishaer; Li, Yuhang; Wang, Kaijun; Chen, Min (Frontiers in Public Health, 2023)
Cytomegalovirus anterior uveitis is the most common ocular inflammatory disease caused by CMV infection. It mainly occurs in middle-aged male with competent immunologic function, and the incidence is higher in Asia. The clinical manifestations vary from Posner Schlossman syndrome, corneal endotheliitis to Fuchs uveitis syndrome, and often accompanied by intraocular hypertension. Secondary glaucoma is a potentially blinding ocular complication, where complicated immunological factors, intraocular inflammation, different types of angle abnormalities and the administration of steroids constitute the pathogenesis. On account of the physical discomfort and the visual impairment that may result in, diagnostic tests like polymerase chain reaction, optical coherence tomography, ocular microscopy, confocal microscopy might help in identifying anterior uveitis caused by other viruses. Antiviral medications combined with anti-inflammatory agents are proved to be effective. If pharmacological therapy cannot reduce intraocular pressure or slow the progression of glaucomatous optic neuropathy, surgical intervention is required as a last resort.